Émergence insoumise: réflexions sur la persistance du racisme systémique envers les femmes autochtones - Wylde, Cyndy (Hannenorak, 2024)
« Émergence insoumise s'ouvre sur un souvenir de l'autrice qui attend un taxi après un colloque : « Non, mais croyez-vous vraiment que moi, une femme des Premières Nations, je vais aller attendre seule le soir, à Val-d'Or? » Ces mots, adressés au gardien qui lui indique que les portes de l'université sont sur le point de fermer, seront le catalyseur d'une réflexion sur le sort réservé aux femmes autochtones, aussi bien dans le milieu carcéral que dans la société canadienne en général. Alternant entre les réminiscences personnelles et les analyses du racisme systémique afin d'aller au-delà des statistiques et des préjugés, cet essai de Cyndy Wylde s'inscrit dans une tradition de littérature de combat, qui bouscule les idées reçues et dynamite le confort et l'indifférence. »
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; féminisme autochtone; phi4336; philosophie; premier cycle; privilèges; périodes historiques; québec; racisme; racisme systémique; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales